2019
DOI: 10.1371/journal.pone.0214170
|View full text |Cite
|
Sign up to set email alerts
|

Frequent sugar feeding behavior by Aedes aegypti in Bamako, Mali makes them ideal candidates for control with attractive toxic sugar baits (ATSB)

Abstract: Background Current tools and strategies are not sufficient to reliably address threats and outbreaks of arboviruses including Zika, dengue, chikungunya, and yellow fever. Hence there is a growing public health challenge to identify the best new control tools to use against the vector Aedes aegypti . In this study, we investigated Ae . aegypti sugar feeding strategies in Bamako, Mali, to determine if this species can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 45 publications
1
44
0
1
Order By: Relevance
“…Early field trials did not show a positive effect of ATSBs on Ae. aegypti [26,27]; however, a recent field trial in Bamako, Mali, showed promising success [31]. The principle barrier to field trial success appears to be the ability to attract Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early field trials did not show a positive effect of ATSBs on Ae. aegypti [26,27]; however, a recent field trial in Bamako, Mali, showed promising success [31]. The principle barrier to field trial success appears to be the ability to attract Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, Ae. aegypti females will readily feed on sugar in the laboratory, and often feed on plant sugars in the wild [28][29][30][31]. However, traditional attractive sugar bait strategies that rely only on fruit volatiles as an attractant are likely insufficient to "lure" highly anthropophilic female Ae.…”
mentioning
confidence: 99%
“…Wells that stayed yellow were considered negative. For a visual indicator of blue colour change see [34].…”
Section: Testing For Sugar and Bait Feedingmentioning
confidence: 99%
“…This could bring the mortality rates of A. aegypti mosquitoes treated with Sh.463 ATSB to 100% in the field. We hope to evaluate this in A. aegypti field trials in the future, as several studies suggest that ATSBs are an effective means of controlling A. aegypti [44,45].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%